The 2nd harmonic signal analysis in Ca-doped Y-123 superconductors: Sensing DC-fields down to 0.5 nT - (:unkn) unknown (ELSEVIER SCIENCE SA, 2012)
We have investigated the DC-field sensing performances of a series of Ca-doped polycrystalline YBa2Cu3O7-delta superconductors. The second harmonic signal generated by applying the AC and DC fields was processed in the designed magnetic sensors. Optimal magnetic sensor properties were achieved on the Ca-doped sample with composition Y0.94Ca0.06Ba2Cu3O7-delta. Small DC-fields down to 0.5 nT could be detected with the transfer functions (dV/dB) of 23,300 V/T. The dynamical range of the sensor can be extended up to similar to 0.5 Oe. The experiments were repeated to test the validity and reproducibility of the results presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: 2nd harmonic signal; High-T-c superconductor; DC-magnetometer; Ultra-low DC field measurements; Magnetic field sensor; GRAIN-BOUNDARIES; FLUXGATE SENSOR; MAGNETOMETER; SENSITIVITY; TRANSPORT